Islam : Between Divine Message and History - Sharafī, ʻAbd al-Majīd (Book collections on Project MUSE., 2005)
Why this book? What can it add to the many works that have already explored Islam as a history, a doctrine, a law, and a code of ethics? The bulk of Islamic thought nowadays is either a repetition of and rumination about what the ancients have already said, or the tackling of partial issues that falls short of a comprehensive view and a theoretical framework. All too often ideology replaces real knowledge. This work attempts to introduce the characteristics of the Mohammedan Mission, with the aspiration to be faithful to its essential purposes and to historical truth at the same time. The author thus illustrates the different ways in which people have understood the Mission and the reasons that led them to those various interpretations. The book presents several alternative interpretations that actually existed but did not enjoy widespread acceptance and popularity. This book looks to the future, attempting to respond to the needs of those who are rapidly becoming integrated into modern life, and to the new generations' aspiration to an Islamic thought adapted to these processes.